Study On Nutrient Levels and Entomological Indicator of Biological Integrity In Fish Culture Ponds of Bhadra Reservoir Project, Karnataka, India: Life Sciences-Environmental Science for better human health - Dr.S.Thirumala; B.Rajappa; Dr.B.R.Kiran (International Journal of Life Science and Pharma Research, 2022)
The supplement levels and organic uprightness of five fish culture ponds were contemplated utilizing water insects and the water quality investigation of the fish ponds as markers from January to December 2011.A sum of 203 insects were recorded with 04 orders and 07 families. There was huge contrast in the plenitude of pond skaters, dragon/damsel fly and whirligig beetles for the five fish ponds (P=0.05). There was no critical distinction in the bounty of water insects and dytiscid beetle (P<0.05). The mean estimations of the physico-chemical parameters of the five fish ponds indicated no noteworthy degree of distinction. The least noteworthy distinction of the bounty of insects demonstrated that ponds 1, 2 and 3 were not favorable for the amphibian bugs inspected. Pond 5 indicated the pinnacle portrayal of all insects inspected. The Carl Pearson connection coefficient demonstrated a solid connection between the quantity of individual of dragon/damsel fly, dytiscid and whirligig beetles and the magnesium focus and Chemical Oxygen demand of the ponds. The pond skater and water bug were adversely associated with the nitrogen substance and temperature of the water bodies. In view of these discoveries the fish culture ponds were considered as decently contaminated biological systems whose contamination load came about predominantly from dumping of poultry/dairy animals’ compost excrement and fish food.